Identification of sulfonyl‐loxoprofen as novel phase 2 conjugate in rat. (19th July 2019) - Shrestha, Riya; Paudel, Sanjita; Cho, Piljoung; Shrestha, Aarajana; Jeong, Tae Cheon; Lee, Eung‐Seok; Lee, Taeho; Lee, Sangkyu
Abstract: Loxoprofen is a prodrug that exerts strong analgesic and anti‐inflammatory effects through its active trans‐alcohol metabolite, which is produced in the liver by carbonyl reductase. Previous metabolic studies have evaluated loxoprofen, but its sulfate and taurine conjugates have not yet been studied. We characterized the metabolomic profile of loxoprofen in rat plasma, urine, and feces using high‐resolution mass spectrometry. We identified 17 metabolites of loxoprofen in the three different biological matrices, 13 of which were detected in plasma and feces and 16 in urine. Amongst these metabolites, two novel taurine conjugates ( M12 and M13) and two novel acyl glucuronides (M14, M15) were identified for the first time in rats. In addition, we detected three novel sulfate conjugates ( M9, M10, and M11) of loxoprofen. Further study of these metabolites of loxoprofen is essential in order to assess their potency and toxicity.